Individualized second language vocabulary learning through a collaborative multimedia platform : a design-based research - Özkan, Gökhan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Incorporation of computer-assisted language learning applications into learning environments through collaborative learning management systems embedded in a hybrid/native mobile app is the subject of this research to apply, evaluate, and improve adult English as Foreign Language (EFL) learners’ digital language learning experiences. This design-based research aims to disseminate the best practice of existing digital services by turning them into a progressive web app (PWA) to be used as a solution to a specific learning environment. Prior to the dissemination step of the research, an exploratory context analysis study was carried out to inform the learning environment (Phase I) in the analysis step. Following that, worldwide language learning apps and platforms were examined, analyzed, and mapped within the scope of international projects to form the pattern of the features of the recent worldwide digital language learning solutions (Phase II). In the design step, a set of studies was conducted to utilize the most effective method considering the parameters of the learning environment where research is carried out. Firstly, the effectiveness of individualized second language vocabulary learning strategy aid through prompts, instead of conventional comprehension exercises, was examined. In addition, research fostering the strategy use by prioritizing the cognitive steps as facilitators was designed to address the critical gap of considering individualized variables in e-learning solutions. In the development stage of the research, the concept of digital language learning and adult EFL learners was introduced to a transformative solution of an innovative hybrid learning environment existing in all digital platforms (Phase III). Lastly, the implementation of the designed tool was compared to conventional methods that have been used in the learning environment and it was found out that the individualization of second language vocabulary learning in e-learning environment was effective when cognitive steps were taken into account and e-learning principles were applied (Phase IV). It was found out that the learners in the experimental group were able to improve their ability to self-regulate their vocabulary learning process, as well as their learning motivation and sense of self-efficacy by utilizing the designed tool. NOTE Keywords : Design-Based Research, Educational Digital Transformation, Progressive Web App, Vocabulary Learning, Instructional Design.
Keywords: Education -- Research.; Educational technology.; Web-based instruction.; Vocabulary -- Study and teaching.; Instructional systems -- Design.; Computer-assisted instruction.; Second language acquisition -- Study and teaching.